EFEKTIVITAS MODEL LEARNING CYCLE 7E BERBANTUAN E-MODUL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMP - Sapta Desty Sugiharti; Nanang Supriadi; Siska Andriani (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This research aimed to findout the effectiveness of learning cycle 7e assisted e-modul to improve critical thinking skill of Junior High School of students. This research used the quasy experimental design with three classed as sample, VII A as first experiment class, VII B as second experiment class, andVII C as control class. The data were used in this research are the result of pretest and n-gain scores. Data were analyzed by one way Anova and Scheffe test. Based on the result of the Scheffe test, it is knownthe models learning is togive the impact of a diffirent order to enhance the ability of the critical thinking skill. The mean of N-Gain at first experiment class was 0,829, at second experiment class was 0,693, and control class was 0,571. Based on the mean of N-Gain, it can be concluded that learning cycle 7e assisted e-modul was the most effective model to improve critical thinking skill of Junior High School students.